Захисні стратегії при торгівлі на фондовій біржі - Бачо Роберт; Robert Bacho; Bacsó Róbert; Ганусич Вероніка; Veronika Hanusych; Hanuszics Veronika; Макарович Вікторія; Vyktorya Makarovych; Makarovics Viktória (ТОВ «ДКС Центр», 2025)
Резюме. У статті проведено системний аналіз ризиків, властивих фондовій біржі, із виокремленням їх на системні та несистемні з точки зору можливості регулювання за допомогою захисних стратегій. Розкрито зміст та обґрунтовано необхідність застосування захисних стратегій для мінімізації втрат та стабілізації фінансових результатів у різних фазах ринку. Проведено класифікацію захисних стратегій за механізмом реалізації, типом впливу на ризик та часовим горизонтом використання. Докладно описано основні види захисних стратегій, зокрема портфельні (стратегічні) та тактичні, розкрито їх зміст, сфери застосування та переваги для інвесторів і трейдерів. У статті також запропоновано узагальнену таблицю класифікації захисних стратегій для практичного використання у побудові системи ризик-менеджменту при торгівлі на фондовій біржі. Підкреслено, що впровадження комплексу захисних стратегій формує основу стійкого та ефективного інвестиційного процесу в умовах ринкової турбулентності.

Abstract. This article presents a comprehensive study ofrisks inherent in stock exchange trading with a clear distinction between systematic and unsystematic risks from the perspective of their potential regulation through protective strategies. The relevance of implementing protective strategies in the investment process is substantiated, emphasizing their role in minimizing losses and stabilizing financial performance under conditions of market volatility and turbulence. A detailed classification of protective strategies is developed, structured by implementation mechanism, the type of risk influence, and the time horizon of application, enabling practitioners and researchers to systematize approaches to risk management within stock market operations.The study elaborates on the essence, areas of application, and key benefits of different protective strategies, dividing them into portfolio-level (long-term protective approaches) and trade-level (tactical protective strategies). Portfolio-level protective strategies include defensive sector rotation, high-dividend strategies, investing in quality stocks, low-beta strategies, asset allocation and rebalancing, global diversification, investments in gold and defensive assets, and maintaining a cash reserve. These strategies contribute to portfolio stability by reducing the exposure to systemic and partially unsystematic risks while ensuring participation in market growth during recovery phases.Trade-level protective strategies encompass the use of stop-loss and trailing stop orders, position sizing, Value-at-Risk (VaR) assessment, and hedging through derivatives, enabling investors to limit potential losses on individual transactions while retaining flexibility to adapt to changing market conditions. The article discusses the practical significance of integrating these strategies within a comprehensive risk management system to achieve stable financial results while preventing the destructive impact of market drawdowns on investment portfolios.A significant focus is placed on the application of derivatives as hedginginstruments, clarifying their role in mitigating price fluctuations of underlying assets, thus protecting investor capital during periods of high volatility. The article concludes that the implementation of a comprehensive system of protective strategies forms the foundation of a sustainable and effective investment process in stock exchange trading, regardless of macroeconomic challenges and market phases. Additionally, the paper offers a generalized table of protective strategies classification for practical use in building robust risk management systems in stock trading.
Protective strategies in stock exchange trading
Весь випуск: https://nayka.com.ua/index.php/ee/issue/view/234
Keywords: фондова біржа; ризик-менеджмент; захисні стратегії; системні ризики; несистемні ризики